Analysis of CT Numbers in Thoracic CT Scan Image Segmentation and Spirometry on Pulmonary Vital Capacity - Suryo Saputro, Annila; Latifah, Lenny; Masrochah, Siti (Journal of World Science, 2023)
This research aims to analyze the correct CT Number to calculate the capacity volume of vital lungs using process segmentation image CT Scans. Compare results from capacity volume vital lungs on segmentation with results measurement volume capacity vital from spirometry. The research method used is an applied experiment that compares the results of lung vital capacity volume in segmentation with the results of vital capacity volume measurements from spirometry. Testing is carried out by calculating each volume on the CT Number used in segmentation and then comparing it with results from spirometry. Analysis data use test Correlation Pearson And Test paired Q Test Results study show that application segmentation image CT Scans with CT Numbers -850 HU up to -950 HU is quite good in calculating the volume of vital lung capacity. There is no significant difference between the results of lung vital capacity volume in segmentation and the results of vital capacity volume measurements in spirometry with a value (p > 0.05) of 0.06. The conclusion of this research is that segmentation image CT Scans of Thorax with the use of CT Numbers -850 HU until -950 HU can considered as an alternative in calculating the volume of vital lung capacity in patients with COPD.